ANALISIS STRUKTUR, PERILAKU DAN KINERJA PASAR (Structure, Conduct and Market Performance)KOMODITI KELAPA DALAM DI KECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI - Ardinata Ardinata; Ahmad Rifai; Deby Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
ABSTRACT The study aimed to analyze the channel, structure, behavior, appearance of the deep coconut market in Tebing Tinggi Timur District, Meranti Islands Regency. This study uses a survey method. Respondents are all marketing institutions involved in marketing coconut. Sampling uses the census method. Data analysis is descriptive and quantitative. The marketing channel is seen from the product flow that the goods go through, the structure is seen from the number of actors, the barriers to entry, concentration ratio, market share and the external index. Market behavior is seen from the practice of price formation, correlation and transmission. Market appearance is seen from marketing margins, efficiency and farmer's share. The research results show the marketing channels, namely (1). Farmers sell to the collector and the collector sells to wholesalers. (2). Farmers sell to big traders and wholesalers sell to factories and abroad. The market structure is an oligopsonist, there are obstacles in and out of the market. The value of the market share at the level of collectors ranges from 0.02-0.13, at the level of wholesalers ranging from 0.06 to 0.22. The value of the herfindahl index at the level of the traders is 0.0884, at the level of wholesalers it is 0.1427. Market behavior shows the end consumer (wholesaler) who determines the price. The price of coconut at the farm level is strongly correlated with the price of coconut at the final consumer level. The value of price transmission elasticity is <1, which means that the price changes at the level of large traders are greater than the price changes at the farmer level. Market appearance, the total marketing margin for channel I is Rp. 904.81, - / Item. Costs and benefits obtained Rp. 175, - / Item and Rp. 730, - / Item. Channel II total marketing margin of Rp. 1,061.81, - / Item. Costs and benefits obtained Rp.195, - / Item and Rp. 867, - / Item. The efficiency of marketing channels I 6.57% and II 6.09% with Farmer's share 66.04%, and 66.82%. Keywords:Coconut, Marketing, Channels, Structure, Behavior, Appearance